A context-aware framework for collaborative activities in pervasive communities - Lima, Christopher (2014)
Pervasive environments involve the interaction of users with the objects that surround them and also other participants. In this way, pervasive communities can lead the user to participate beyond traditional pervasive spaces, enabling the cooperation among groups taking into account not only individual interests, but also the collective and social context. In this study, the authors explore the potential of using context-aware information in CSCW application in order to support collaboration in pervasive environments. In particular this paper describes the approach used in the design and development of a context-aware framework utilizing users' context information interpretation for behaviour adaptation of collaborative applications in pervasive communities.